Health related quality of life in children and adolescents with sickle cell disease in central India - Gupta, Nikita Suresh; Bokade, Chandrakant M. (International Journal of Contemporary Pediatrics, 2022)
Background: Sickle cell disease (SCD) is major health problem in central India. This is a single centre study conducted to assess the health-related quality of life (HRQOL) in children and adolescent with homozygous (SS pattern) and heterozygous (AS pattern) SCD with respect to healthy children. Methods: This is a case control study conducted in a tertiary care hospital. Study group included total of 150 children and adolescents with SS pattern and AS pattern. HRQOL of the children in study group was compared with demographically matched 100 healthy children in comparison group. WHO-QOL BREF questionnaire was administered to both the groups to measure their HRQOL in various domains. Multivariable linear regression was used to account for socio-demographic factors influencing HRQOL. Results: The WHO-QOL BREF scores of children with SS pattern were significantly lower than those obtained in the AS pattern and healthy children (p<0.001) in all studied domains (physical, psychological, social and environmental). The domain scores of HRQOL in children with AS pattern didn’t differ significantly as compared to healthy children. Results also highlighted that along with severity of disease, various demographic characteristics like age, gender, locality and socioeconomic status had significant impact on various domains of HRQOL Conclusions: SCD has detrimental effect on HRQOL of growing children and adolescent that is compounded by various demographic and socio-environmental factors in a developing country.